Optimasi Kinerja Pompa Sentrifugal Produk Lokal dengan Modifikasi Impeler dan Analisis visualisasi Aliran - Soeadgihardo Siswantoro; S Sutrisno (Faculty of Engineering, Universitas Gadjah Mada, 2003)
A preliminary efort to inrprove an impeller design for domestic centrifugal pump with 165 mm outlet diameter, semi open impeller has been initiated implementing flow visualization method. The study was focused on several impellers having different inlet and outlet angles, each of them has the same blade thickness.A facitity has been constructed to measure the performance for those impellers at similar speed, 200b rpm. The visualization technique applied in the study was wet paint method applying point on the surface of the impellers with several layers of dffirent colors and wetness.Impellers hwing optimum inlet ond outlet angles have been identified.Keywords : impeller, flow visualization